1995
DOI: 10.1093/intimm/7.8.1243
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cultured CD40-activated B lymphocytes differentiate into plasma cells in response to IL-10 but not IL-4

Abstract: We compared the effects of IL-10 and IL-4 on the functions of B lymphocytes triggered through their CD40. During the initial phase, IL-10 was as potent as IL-4 in inducing the expansion of viable B cells. Then, cellular expansion slowed down and after approximately 3 weeks the number of B cells started to decline. While the combination of IL-10 and IL-4 was synergistic during the first 2 weeks of culture, B cell recovery declined after 3 weeks, indicating that IL-10 prevails over IL-4. Those effects were not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 0 publications
5
75
0
Order By: Relevance
“…Subsequently it was reported that, although IL10 could induce CD40-activated B cells to differentiate into plasma cells, IL4 did not have this effect (Rousset et al, 1995). Using this system with murine fibroblasts expressing CD40L (CD154) in combination with recombinant IL4 (Figure 1a), we have consistently found that CD19-positive peripheral human B cells actively proliferate in culture for only 3-4 weeks before arresting and showing signs of terminal differentiation (manuscript in preparation).…”
Section: Resultsmentioning
confidence: 73%
“…Subsequently it was reported that, although IL10 could induce CD40-activated B cells to differentiate into plasma cells, IL4 did not have this effect (Rousset et al, 1995). Using this system with murine fibroblasts expressing CD40L (CD154) in combination with recombinant IL4 (Figure 1a), we have consistently found that CD19-positive peripheral human B cells actively proliferate in culture for only 3-4 weeks before arresting and showing signs of terminal differentiation (manuscript in preparation).…”
Section: Resultsmentioning
confidence: 73%
“…For instance, after stimulation with the combination of the B cell mitogen SAC, IL-2, and IL-10, accumulation of activated cells in G 1 and subsequent Ig secretion take place after a single round of proliferation, whereas G 1 arrest and Ig secretion observed after activation with CD40 and IL-10 occur after several rounds of proliferation, leading to quantifiable cell growth ( Fig. 6B) (40,41). Hasbold et al reported that after CD40 and IL-4 stimulation of murine B cells, IgG secretion was observed after three rounds of proliferation, whereas IgE production was only evidenced after five proliferative rounds (42).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that they are the products of a recent clonal expansion that probably occurred in a GC, given the presence of unique mutations. This expansion may be explained by increased IL-10, a major plasma cell differentiation factor (56). Indeed, high levels of IL-10 are found in the serum of SLE patients, and treatment of these patients with anti-IL-10 Abs has shown beneficial effects (57-59).…”
Section: Blood B Cell Subsets In Children With Slementioning
confidence: 99%